Dispersing hydrophilic nanoparticles in hydrophobic polymers: HDPE/ZnO nanocomposites by a novel template-based approach - G. Filippone; M. Salzano de Luna; M. Galizia; D. Acierno; R. Rosa; C. Leonelli; J. Wojnarowicz; W. Lojkowski (eXPRESS Polymer Letters, 2014)
The efficiency of a novel template-based approach for the dispersion of hydrophilic nanoparticles within hydrophobic polymer matrices is investigated. The procedure envisages the permeation of a well dispersed nanoparticle suspension inside a micro-porous matrix, obtained through selective extraction of a sacrificial phase from a finely interpenetrated co-continuous polymer blend. Specifically, a blend of high density polyethylene (HDPE) and polyethylene oxide (PEO) at 50/50 wt% is prepared by melt mixing. The addition of small amounts of organo-clay promotes the necessary refinement of the blend morphology. Once removed the PEO, the micro-porous HDPE matrix is dipped in a colloidal suspension of zinc oxide nanoparticles which exhibits low interfacial tension with HDPE. A system prepared by traditional melt mixing is used as reference. Melt- and solid-state viscoelastic measurements reveal a good quality of the filler dispersion despite the uneven distribution on micro-scale. The latter can be capitalized to minimize the filler content to attain a certain improvement of the material properties or to design nano-structured polymer composites.